15. KONSENTRASI PROTEIN ANTIGEN EKSKRETORI/SEKRETORI DAN SOMATIK PADA Fasciola gigantica DAN Eurytrema pancreaticum The Protein Concentration of Excretory/Secretory and Somatic Antigen from Fasciola gigantica and Eurytrema pancreaticum - Muhammad Hambal (Universitas Syiah Kuala, 2016)
The study was aimed at finding out the difference of protein content between excretory/secretory and somatic antigen of Fasciola gigantica as well as between excretory/secretory of Fasciola gigantica and Eurytrema pancreaticum. As many as 32 Fasciola gigantica and 30 Eurytrema pancreaticum were placed into 80 ml Roswell Park Memorial Institute (RPMI) 1640 and incubated for 6 hours. Excretory/secretory as well as somatic antigen was isolated and the concentration of protein was determined, using Lowry method. The result revealed the different of protein concentration. The concentrations of excretory/secretory antigen protein in Fasciola gigantica and Eurytrema pancreaticum were 3.386 mg/ml and 0.128, mg/ml respectively. The concentrations of somatic protein and Fasciola gigantica and Eurytrema pancreaticum were 8.028 mg/ml and 0.534 mg/ml, respectively. It can be concluded that the protein concentration from somatic tissue of Fasciola gigantica and Eurytrema pancreaticum is higher than the protein concentration from excretory/secretory of Fasciola gigantica and Eurytrema pancreaticum. The protein concentration from excerory/secretory antigen of Fasciola gigantica is higher than the protein concentration from excretory/secretory antigen of Eurytrema pancreaticum. ____________________________________________________________________________________________________________________ Key words: Fasciola gigantica, Eurytrema pancreaticum, protein concentation